Tailoring of Titanium Dioxide Thin Film in Dual Radiofrequency Plasma Enhanced Pulsed Laser Deposition - Singh, D (Elsevier B.V., 2025)
Efficient and cost-effective methods to create photovoltaic materials are constantly being sought, with metal oxides like TiO2 playing a key role in this field. In this study, TiO2 thin films were grown on glass substrates using a dual radiofrequency (RF) plasma-enhanced pulsed laser deposition (PLD) system with a thermal budget that remained below 400 °C. The physical, chemical, and optical properties of the deposited thin films were studied as a function of low- and high-RF powers as well as deposition time. These parameters were found to impact the proportion of anatase and rutile phase and their crystallinity, as well as the oxygen vacancy concentration and band gap energy. These findings demonstrated the utility of dual RF plasma-enhanced PLD for precise modulation of TiO2 thin-films, offering promising applications in photovoltaics and photocatalysis. © 2025 Elsevier B.V.